2019
DOI: 10.5194/gmd-12-363-2019
|View full text |Cite
|
Sign up to set email alerts
|

Nemo-Nordic 1.0: a NEMO-based ocean model for the Baltic and North seas – research and operational applications

Abstract: Abstract. We present Nemo-Nordic, a Baltic and North Sea model based on the NEMO ocean engine. Surrounded by highly industrialized countries, the Baltic and North seas and their assets associated with shipping, fishing and tourism are vulnerable to anthropogenic pressure and climate change. Ocean models providing reliable forecasts and enabling climatic studies are important tools for the shipping infrastructure and to get a better understanding of the effects of climate change on the marine ecosystems. Nemo-N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 84 publications
0
86
0
Order By: Relevance
“…The dispersal of organisms (eggs, spores, larvae, or rafting algae) was modelled with a Lagrangian particle‐tracking model driven off‐line with flow fields from an ocean circulation model. The stored ocean transport data were produced with the NEMO‐Nordic model (Hordoir et al, ), which is a regional configuration of the NEMO ocean engine (Madec, ) covering the Baltic Sea and the eastern North Sea. The model has a horizontal spatial resolution of 3.7 km, and 84 vertical levels with depth intervals of 3 m at the surface and 23 m for the deepest layers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dispersal of organisms (eggs, spores, larvae, or rafting algae) was modelled with a Lagrangian particle‐tracking model driven off‐line with flow fields from an ocean circulation model. The stored ocean transport data were produced with the NEMO‐Nordic model (Hordoir et al, ), which is a regional configuration of the NEMO ocean engine (Madec, ) covering the Baltic Sea and the eastern North Sea. The model has a horizontal spatial resolution of 3.7 km, and 84 vertical levels with depth intervals of 3 m at the surface and 23 m for the deepest layers.…”
Section: Methodsmentioning
confidence: 99%
“…Climatological data from a number of different databases for the Baltic Sea and the North Sea provided freshwater runoff. Validation of the NEMO‐Nordic model has showed that the model is able to correctly represent the sea surface height, both tidally induced and wind driven (Hordoir et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…All results below from the biophysical model are referred to as "connectivity," to be distinguished from results obtained from genetic data, which are referred to using the terms "gene flow" and "population structure." The biophysical model is based on the oceanographic circulation model NEMO-Nordic that produces water velocity fields with spatial resolution of 3.7 km in the horizontal and 3-12 m in the vertical, and a temporal resolution of 3 hr (for details, see Hordoir et al, 2019).…”
Section: Biophysical Modelmentioning
confidence: 99%
“…The coupled simulation evaluated in our study consist of three main models, CCLM responsible for the atmosphere and land surface, NEMO-MED12 [29] for the Mediterranean Sea and NEMO-NORDIC [30] for the Baltic and North Seas. Moreover, NEMO-NORDIC also includes a sea ice model named LIM3 (Louvain-la-Neuve sea ice model) [31].…”
Section: Coupled Simulationmentioning
confidence: 99%